Isolation and identification of Streptococcus mutans from periapical lesion of extracted teeth - Hasan, Ahmad Orkhan; Sulaiman, Saad Mohammed; Naji, Noora Abdulrazzaq (International Journal of Psychosocial Rehabilitation, 2020)
A cross-sectional study done on 200 patients (rang from 20-55 years) attended to dentist unit in Azadi teaching hospital in Kirkuk city-Iraq from March 2018 to April 2019. After successful assessment of available laboratory tests and preparation of patients. Sample of periapical lesion were collected from all patients one week after the teeth extraction for bacteriological examination of these swabs for evaluation the antibiotic resistance of S. mutans and reporting of the most appropriative antibiotic used for eradication of this causative agent of wound infection. Sampling of the periapical lesion in the wing was done by the resident dentist using the sterile swab sticks according to the guidelines in the sections. Swabs collected on blood agar and McConkey agar were wiped out by sterile sterilization ring. Agar plates are incubated at 37 ° for 24-48 hours. The bacterial colonies were then stained on an agar plate and subjected to biochemical tests to identify and classify them. The study showed that 12.5% (25 of 200) of patients enrolled in the study had positive culture of periapical lesion swab and 87.5% was negative , the study found that 20% of patients with positive periapical lesion culture were diabetics comparing with 8.57% of patients with negative periapical lesion and 12% of patients with positive wound culture were smokers comparing with 6.86% of patients with negative wound culture. The study showed that 68% of isolated bacteria from periapical lesion culture was S. mutans followed by 20% S. aureus and the lowest rate of isolated bacteria was E. coli (12%). The study showed that all isolates of S. mutans (100%) were resistant to ciprofloxacin, tetracycline and levofloxacin followed by 94.12% of isolates were resistant to gentamicin and tobramycin as well as 88.24% of isolates were resistant to ceftazidime and amoxicillin.